Feasibility of a mindfulness-based intervention for stress reduction and resilience for medical students at a large teaching hospital and medical campus in the western cape : a randomised controlled, comparative trial with supportive counselling - Boyd, Nicola Lindy (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.